2016
DOI: 10.1103/physrevc.93.054910
|View full text |Cite
|
Sign up to set email alerts
|

Tests of constituent-quark generation methods which maintain both the nucleon center of mass and the desired radial distribution in Monte Carlo Glauber models

Abstract: Several methods of generating three constituent-quarks in a nucleon are evaluated which explicitly maintain the nucleon's center of mass and desired radial distribution and can be used within Monte Carlo Glauber frameworks. The geometric models provided by each method are used to generate distributions over the Number of Constituent Quark Participants (Nqp) in p + p, d+Au and Au+Au collisions. The results are compared with each other and to a previous result of Nqp calculations, without this explicit constrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…The wounded quark scaling also works for the SPS energy range [15]. More recent studies were reported in [16][17][18][19].Our results for particle production at midrapidity are shown in Fig. 1.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The wounded quark scaling also works for the SPS energy range [15]. More recent studies were reported in [16][17][18][19].Our results for particle production at midrapidity are shown in Fig. 1.…”
supporting
confidence: 62%
“…The wounded quark scaling also works for the SPS energy range [15]. More recent studies were reported in [16][17][18][19].…”
mentioning
confidence: 99%
“…Shifting the nucleons by the average displacement, however, introduces a distortion of the radial profile, which increases with decreasing degrees of freedom. This effect has been recently discussed in Glauber approaches accounting for subnucleonic degrees of freedom, where the distortion is particularly large when only three partons (quarks) are distributed inside a proton [64]. For a 208 Pb nucleus, the width of the center-of-mass shift is about 0.2 fm in each direction, and the effect of the associated distortions have so far been ignored.…”
Section: Recenteringmentioning
confidence: 99%
“…Without resort to non-perturbative physics, it is difficult to justify this model, since particle production is thought to be perturbative in the regime where partons are good degrees of freedom, and perturbative dynamics does not scale with participants. But phenomenologically a wounded quark model appears to work [22][23][24][25] well enough that fusing this with the geometrical deep inelastic scattering warrants a try.…”
Section: Partonic Nuclear Dynamics and Limiting Fragmentationmentioning
confidence: 99%
“…We then argue that a currently popular model capable of bringing the applicability of limiting fragmentation to LHC energies and varying system sizes, provided it is indeed confirmed experimentally, is a "wounded parton model", with Glauber wounded partons [22][23][24][25][26] smeared in rapidity space according to Bjorken scaling. We conclude with some experimental considerations regarding this observable.…”
Section: Introductionmentioning
confidence: 99%